NILAI-NILAI EDUKATIF (NILAI KEPRIBADIAN DAN SOSIAL) DALAM NOVEL MADOGIWA NO TOTTO-CHAN KARYA TETSUKO KUROYANAGI - Murdiani, Heri (Japanese Literature, 2013)
Murdiani, Heri. “Nilai-Nilai Edukatif (Nilai Kepribadian dan Nilai Sosial) Dalam Novel Madogiwano Totto-Chan Karya Tetsukou Kuroyanagi”. Thesis. Japanese Literature Department. Faculty of Humanities Diponegoro University. Pembimbing I. Yudiono KS, SU. Pembimbing II. Fajria Noviana, SS, M.Hum. Madogiwano Totto-Chan is a novel which tells about the author’s experience, Tetsukou Kuroyanagi when she studied in Tomoe Gakuen. When she was young, her nick name was Totto-chan. Her teachers thought that Totto-chan was a naughty girl. In fact, she was a cheerful girl, but had great curiosity. She was kicked out of her school because she used to make noise at her class. Her mother then enrolled Totto-chan to Tomoe Gakuen. In that school, all students studied in a carriage. In Tomoe, the students were free to choose the sequence of lessons that they liked. Because this school was unique, Totto-chan felt at home. Day by day, Totto-chan felt happy and experienced unexpected things. The school story ended when Tomoe Gakuen was burned down by the bomb in World War II. This study aims to find out the generic structure of the novel, including the theme, the characters and characterization, the plot, the settings, and the central narrative. It also aims to seek the educative values (personality and social values) in Madogiwa no Totto-Chan. The educative values found in this novel was then analyzed to decide which ones can be applied in educational field. Keywords : Nilai-Nilai Edukatif, Madogiwano Totto-chan novel.